2008
DOI: 10.1142/s0217751x08039384
|View full text |Cite
|
Sign up to set email alerts
|

Ghosts and Tachyons in the Fifth Dimension

Abstract: We present several solutions for the five dimensional gravity models in the presence of bulk ghosts and tachyons to argue that these "troublesome" fields can be a useful modelbuilding tool. The ghost-like signature of the kinetic term for a bulk scalar creates a minimum in the scale factor, removing the necessity for a negative tension brane in models with the compactified fifth dimension. It is shown that the model with the positive tension branes and a ghost field in the bulk leads to the radion stabilizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Further it was shown that a bulk scalar field whose sign can vary between regular (positive) and ghost (negative) can be used to model both positive and negative tension branes. Also, there are certain configurations of the bulk ghost fields of reference [51] which lead to stronger localization of gravity than the original brane models. In references [52,53] it is shown that the two brane model of [1,2,3,4] is stabilized by a ghost/tachyon bulk field, while for a regular bulk scalar field the two brane model is unstable.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Further it was shown that a bulk scalar field whose sign can vary between regular (positive) and ghost (negative) can be used to model both positive and negative tension branes. Also, there are certain configurations of the bulk ghost fields of reference [51] which lead to stronger localization of gravity than the original brane models. In references [52,53] it is shown that the two brane model of [1,2,3,4] is stabilized by a ghost/tachyon bulk field, while for a regular bulk scalar field the two brane model is unstable.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…5D standing wave braneworld [13][14][15] is generated by gravity coupled to a non-self-interacting scalar phantom-like field (different brane models with phantom fields can be found in [38][39][40][41][42][43]), which depends on time and propagates in the bulk. The action of the model has the form:…”
Section: Background Solutionmentioning
confidence: 99%
“…Note that, as a consequence of (4.17) and (4.21), in our setup the right fermionic modes are absent on the brane: ρ(r)| r→±0 = 0 . In the second limited region -far away from the brane, 23) and the equation (4.18) takes the asymptotic form:…”
Section: Localization Of Fermionsmentioning
confidence: 99%